Lower Extremity Deformity Management in MPS IVA, Morquio-Brailsford Syndrome: Preliminary Report of Hemiepiphysiodesis Correction of Genu Valgum. Issue 4 (June 2016) - Cooper, George A.; Southorn, Thomas; Eastwood, Deborah M.; Bache, C. Edward
Abstract : Background: Morquio-Brailsford syndrome or mucopolysaccharidosis type IV-A (MPS IV-A) is an inherited metabolic disease in which skeletal deformities can be extreme. An international registry has shown that 46% of patients are unable to walk 200 m and 30% use a wheelchair. Lower limb surgery is performed to restore alignment with the expectation of maintaining mobility. We are, however, not aware of reports correlating function with alignment. This study assesses the role of orthopaedic intervention with reference to anatomic and functional outcome in MPS IV-A: specifically hemiepiphysiodesis correction of genu valgum. Methods: Interrogation of the MPS patient database identified 63 patients. Patient demographic and radiographic data were collected along with information on deformity, correction, mobility, and genotype. Genu valgum was assessed by intermalleolar distance and mobility by a standardized 6-minute walk test. Sequential hip anatomy was assessed radiographically. Results: Twenty-six surgical hemiepiphysiodesis episodes were performed on 23 patients. There were no cases of implant failure, loosening, or infection. The average intermalleolar distance reduction was 6.12 cm (paired t test, P =0.0001) (95% confidence interval, 7.6-4.7 cm) and the mean change in 6-minute walk test was +69.5 m ( P =0.0339). There was no correlation between hip subluxation/dislocation and mobility (Fisher exact test, P =1.000), although hip parameters deteriorated over time. Three patients required repeat 8-plate insertion and 1 a femoral osteotomy. Conclusions: Eight-plate hemiepiphysiodesis correction of genu valgum in MPS IV-A is an effective treatment with low complication rates. The insult of surgery is minimal compared with that of osteotomy which can reduce mobility further. Our outcomes suggest that mobility is maintained or improved even in severe genotypes where mobility typically worsens. We have found hip pathology to be less debilitating, but further studies are needed to assess the effect of genu valgum correction upon femoral head subluxation and collapse. We suggest hemiepiphysiodesis should be considered as part of the treatment strategy for limb alignment in MPS IV-A patients, depending on remaining growth, mobility status, and genotype. Level of Evidence: Level IV—therapeutic case series.